Strategi Kepala Sekolah Dalam Optimalisasi Pembiayaan di SDN 1 Medanglayang - Sri Mulyanti; Risbon Sianturi; Sarah Fauziah; Heni Widiani; Deni Ramdani (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
Education is the acquisition of knowledge, skills, and habits by a group of people, which are transmitted from one generation to the next through teaching, training, or research. Training is often carried out under the guidance of another person, but self-taught is also possible. This research method is qualitative research with a descriptive-analytic case study research design. Analytical descriptive according to Cresswell (2015), descriptive-analytical information compiled by researchers at research locations such as observations, interview results, shooting results, document analysis, and field notes, which were compiled by researchers at research locations, not expressed in forms and pictures. The results of this study are strategies that can overcome these problems, namely: 1) Multipurpose funds (teacher welfare) are not channeled, 2) Funds entrusted by parents of class VI students, 3) Personal funds to school principals, and 4) Private funds to treasurers